Do the poor benefit from devolution policies?: evidence from Malawi’s forest co-management program - Jumbe, C.B.L.; Angelsen, A. (2006)
Do local people, especially vulnerable households, benefit from devolution of forest management? The authors apply the propensity-score matching and decomposition techniques on household data from Chimaliro and Liwonde forest reserves under the pilot forest co-management program in Malawi. After controlling for selection bias, they find that while the program raises forest income for participants in Chimaliro, it reduces revenue for participants in Liwonde. Interestingly, results indicate that the program raises forest income for female and low-income participants, although male and richer participants capture more benefits due to discrimination and endowment differences accounting for 100% and 60%of the inter-group income disparity, respectively.